Engineering a deformation-free plastic spiral inertial microfluidic system for CHO cell clarification in biomanufacturing. Issue 2 (21st December 2021) - Jeon, Hyungkook; Kwon, Taehong; Yoon, Junghyo; Han, Jongyoon
Abstract : A deformation-free and mass-producible plastic spiral inertial microfluidic device was developed, which provides continuous, clogging-free, and industry-level-throughput cell manipulation. Abstract : Inertial microfluidics has enabled many impactful high throughput applications. However, devices fabricated in soft elastomer ( i.e., polydimethylsiloxane (PDMS)) suffer reliability issues due to significant deformation generated by the high pressure and flow rates in inertial microfluidics. In this paper, we demonstrated deformation-free and mass-producible plastic spiral inertial microfluidic devices for high-throughput cell separation applications. The design of deformable PDMS spiral devices was translated to their plastic version by compensating for the channel deformation in the PDMS devices, analyzed by numerical simulation and confocal imaging methods. The developed plastic spiral devices showed similar performance to their original PDMS devices for blood separation and Chinese hamster ovary (CHO) cell retention. Furthermore, using a multiplexed plastic spiral unit containing 100 spirals, we successfully demonstrated ultra-high-throughput cell clarification (at a processing rate of 1 L min −1 ) with a high cell-clarification efficiency of ∼99% (at the cell density changing from ∼2 to ∼10 × 10 6 cells mL −1 ). Benefitting from the continuous and clogging-free separation with an industry-level throughput, the cell clarification device could be a critical breakthrough for the production of therapeutic biologics such as antibodies or vaccines, impacting biomanufacturing in general.